LAW ENFORCEMENT IN THE FIELD OF HEALTH BASED ON LAW NUMBER 17 OF 2023 ON HEALTH - Firdaus, Firdaus (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Violations of the law in the field of health services take various forms, including violations of criminal, civil, and administrative laws. Of course, it is important to enforce the law against these violations to protect the rights and losses experienced by patients or their families. Efforts made to enforce the law against violations in the field of health services are in order to improve health services in hospitals carried out by nurses, doctors, and administrative services, so that in the future they will be better and can maintain the credibility of services in the health sector. Sanctions for violators of health services in hospitals, whether done intentionally or unintentionally, can be in the form of imprisonment, fines, compensation, revocation of permits, code of ethics sanctions and so on, which are forms of accountability for violations committed by the hospital and related parties. Therefore, it is also necessary to make efforts to prevent violations of health services, including revising regulations in the field of health services, improving the quality of services through training and education, conducting intensive and strict supervision, and implementing and enforcing the law firmly.